2015
DOI: 10.1038/nature14025
|View full text |Cite
|
Sign up to set email alerts
|

Optically addressable nuclear spins in a solid with a six-hour coherence time

Abstract: Space-like separation of entangled quantum states is a central concept in fundamental investigations of quantum mechanics and in quantum communication applications. Optical approaches are ubiquitous in the distribution of entanglement because entangled photons are easy to generate and transmit. However, extending this direct distribution beyond a range of a few hundred kilometres to a worldwide network is prohibited by losses associated with scattering, diffraction and absorption during transmission. A proposa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
622
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 630 publications
(666 citation statements)
references
References 29 publications
14
622
0
10
Order By: Relevance
“…We use the yellow 7 F 0 → 5 D 0 transition at 580.04 nm, which has an extremely narrow optical homogeneous broadening [40] at cryogenic temperatures. It also presents long spin coherence times [41][42][43]. The isotopically enriched 151 Eu 3+ doping results in a larger optical depth as compared to a natural abundance of Eu 3+ isotopes [44].…”
Section: A Experimental Setupmentioning
confidence: 99%
“…We use the yellow 7 F 0 → 5 D 0 transition at 580.04 nm, which has an extremely narrow optical homogeneous broadening [40] at cryogenic temperatures. It also presents long spin coherence times [41][42][43]. The isotopically enriched 151 Eu 3+ doping results in a larger optical depth as compared to a natural abundance of Eu 3+ isotopes [44].…”
Section: A Experimental Setupmentioning
confidence: 99%
“…Further, teleportation of quantum logic gates, a key element in distributed quantum computing schemes, is also possible assisted by shared multiparticle entangled states 5,6 . Given the rapid progress on long-live quantum memories 26 and efficient light-matter interface 27 , more sophisticated space-scale teleportation can be realized and is expected to play a key role in the future distributed quantum internet. The highest loss is ~52 dB at a distance of 1400 km, when the satellite is at 14.5°a ngle.…”
mentioning
confidence: 99%
“…The photon is emitted due to a quantum interference effect between each absorption line of the comb. Ensembles of rare-earth-ions are particularly suited for atomic frequency comb quantum memories due to the long coherence times of both the optical (100s of microseconds [62,63]) and spin (up to milliseconds [62,63] or even seconds [64]) transitions in conjunction with level structures that allow for efficient atomic frequency combs over ∼MHz bandwidths [11,62,63].…”
Section: State-of-the-art Quantum Memoriesmentioning
confidence: 99%
“…Taking into consideration the technical challenges of obtaining both high efficiency and low noise in a rare-earth-ion-doped crystal-based atomic frequency comb system, in section 3 we explore the possibility of using several (spectral) modes to overcome the no-memory bound. Note that coherence times of 6 hours [64] and one minute [67] have been measured using magnetically-insensitive ground-level transitions of 151 Eu:Y 2 SiO 5 and Pr:Y 2 SiO 5 , respectively. However, it has yet to be shown that these coherence times can be combined with the possibility of efficient and broadband storage, hence these transitions may not be suitable for MA-MDI-QKD.…”
Section: State-of-the-art Quantum Memoriesmentioning
confidence: 99%